2012
DOI: 10.1111/ibi.12007
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐avoidance behaviour in a nocturnal petrel exposed to a novel predator

Abstract: Many species of bird recognize acoustic and visual cues given by their predators and have complex defence adaptations to reduce predation risk. Recognition of threats posed by specific predators and specialized anti-predation behaviours are common. In this study we investigated predator recognition and anti-predation behaviours in a pelagic seabird, Leach's Storm-petrel Oceanodroma leucorhoa, at a site where predation risk from Great Skuas Stercorarius skua is exceptionally high. Leach's Storm-petrels breed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
0
16
2
Order By: Relevance
“…This apparent response to anthropogenic light levels is in contrast to the lack of significant moonlight effect. Moon effects can be masked by cloud cover (Miles et al ), but our results showed no association between call rates and the lunar cycle even in clear conditions. The influence of moon on calling levels is uncertain in brown kiwi, with several reports that they are less vocal in bright moon periods (Clark , Colbourne and Kleinpaste ), but others finding no effect (Pierce and Westbrooke ).…”
Section: Discussioncontrasting
confidence: 74%
“…This apparent response to anthropogenic light levels is in contrast to the lack of significant moonlight effect. Moon effects can be masked by cloud cover (Miles et al ), but our results showed no association between call rates and the lunar cycle even in clear conditions. The influence of moon on calling levels is uncertain in brown kiwi, with several reports that they are less vocal in bright moon periods (Clark , Colbourne and Kleinpaste ), but others finding no effect (Pierce and Westbrooke ).…”
Section: Discussioncontrasting
confidence: 74%
“…Poor quality was mainly due to precipitation and low light levels on cloudy moonless nights. Fewer activity events were detected when image quality was poor, even though Storm Petrels may favour dark nights for entering or leaving burrows (Miles et al 2013). Infra-red filming may therefore greatly underestimate activity levels on the darkest nights.…”
Section: Filmed Storm Petrel Activity As a Predictor Of Aos Densitymentioning
confidence: 97%
“…• Avoid or ignore beneficial options (e.g., avoid high quality restored habitats, Hale and Swearer, 2017; or novel foods, Pearse et al, 2013); • Approach or fail to avoid stimuli with negative fitness outcomes (e.g., consume novel toxic foods, Crossland et al, 2008; oviposit on invasive plants, Keeler and Chew, 2008; or allow close contact with novel predators, Miles et al, 2013;or pathogens, Bouwman and Hawley, 2010); • Fail to ignore neutral stimuli (e.g., avoid or be stressed by passing tourists unnecessarily, Ellenberg et al, 2007).…”
Section: The Conceptual Framework: Breaking Down the Steps Required Fmentioning
confidence: 99%
“…The errors that cause traps can go "both ways." They include the underuse of good habitat or resources (Gilroy and Sutherland, 2007), and the overuse of poor habitat (Robertson et al, 2013) or toxic "foods" (e.g., cane toads, Shine, 2010); as well as the underavoidance of novel predators Miles et al, 2013), and the over-avoidance of situations and habitats that are safe, but appear dangerous (Hale and Swearer, 2017;Trimmer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%